PENDAMPINGAN BELAJAR MATEMATIKA PADA MATERI PERKALIAN MENGGUNAKAN MEDIA PEMBELAJARAN KINCIR PERKALIAN DI SDN 213 SABBANG - trianaadr, suci; nurwahida, rusdam; dhanyfkbs, dhany (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIM Sinjai, 2023)
This service aims to introduce students to the multiplication wheel media and help students at SDN 213 Sabbang improve their knowledge and abilities in terms of learning so that students don't get bored while studying. The results of this service show that there has been an increase in understanding of multiplication material and enthusiasm for learning mathematics.